Epizootics of Malaysian cultured freshwater pond fishes by Piscinoodinium pillulare (Schaperclaus 1954) Lom 1981 - Shaharom-Harrison, F.M.; Anderson, I.G.; Siti, A.Z.; Shazili, Noor A.M.; Ang, K.J.; Azmi, T.I. (Elsevier Science, 1990)
A series of nine epizootics due to the dinoflagellate Piscinoodinium pillulare is reported from Peninsular Malaysia. Although grass carp (Ctenopharyngodon idella), jelawat (Leptobarbus hoevenii), and bighead carp (Aristichthys nobilis) were infested with this parasite, only lampam jawa (Puntius gonionotus) was highly susceptible and suffered mass mortalities as a result of a heavy infestation. Water quality parameters were taken from the affected ponds and water inlets. The temperature range of the pond water was 24.5-31.5°C. The pH range was 5.7-6.3 for the inlet water and 5.7-7.4 for the pond water. Ammonia content of the pond water was 0.04-1.50 mg/l. Scanning electron micrographs showed the ovoid globular shape of the trophonts of P. pillulare. Transmission electron micrographs showed that the theca of Piscinoodinium trophonts consisted of three unit membranes with numerous starch granules, lipid droplets and chloroplasts present in the cytoplasm. Clinical signs comprised a rust-coloured appearance of the skin, showing the presence of Piscinoodinium, and a dense covering of mucus. Head and dorsal regions were darker than normal and there were petechia on the body with a slight inflammation at the basal portion of the fins. Histopathological changes were manifested by fusion of the gill lamellae and trophonts were apparent in cavities created by fusion of adjacent lamellae.